Validation and economic analysis of adaptable integrated management technology against root-knot nematode (Meloidogyne graminicola) in rice (Oryza sativa) with farmers’ participatory approach - SOMASEKHARA, Y; SEGHAL, MUKESH; RAVICHANDRA, N G; SIDDEGOWDA, D K; JAIN, R K; MAHADEVU, P; RAVINDRA, K R; RAMAKRISHNA, RAMAKRISHNA; SARDANA, H R (The Indian Journal of Agricultural Sciences, 2012)
Wider area validation and economic analysis of adaptable integrated root-knot nematode (Meloidogyne graminicola) management technology in rice (Oryza sativa L.) in farmers’ participatory approach was carried out in adopted village Akkihebbalu, K.R.Pet, Mandya district, Karnataka during 2008, 2009 and 2010 in the 437 acre area covering 167 farmers’ families. Integrated nematode management technology (INMT) for rice comprised raising rice nursery in cabrofuran (0.3g a.i/m2) treated beds followed by its field application @ 1 kg ai/ha 40 days after transplanting (T1) or applying Pseudomonas fluorescence @ 20 g/m2 in soil nursery (T2) or seed treatment of rice with Trichoderma viride @ 4 g/kg seed in nursery (T3). The adoption of INMT resulted in reducing the nematode population from 320 J2/200 c.c soil as initial nematode population to 135(T1) ,165 (T2) and 192 (T3)/200 cc of soil in the respective treatments thereby leading to increase yield 4.72 tonnes/ha, 4.67 tonnes/ha and 4.29 tonnes/ha in T1,T2 and T3 respectively, in comparison to 3.81 tonnes/ha in untreated control (T4).